Peran Guru Sebagai Transformasi Digital dalam Persimpangan Script Agama dan Scroll Teknologi - Rosa Safitri; Ulfatus Sholeha; Anjaliatul Luaily; Fatichatus Sa'diyah (Journal Islamic Studies of Muhammadiyah, 2026)
This article examines the evolving role of teachers in the digital era, where they function not merely as knowledge transmitters but as agents of ecological transformation. The study argues that in addressing technological disruption and moral crises, teachers must undertake two simultaneous actions: digitalize faith by integrating spiritual values into the digital realm, and strengthen ethics by reinforcing the foundation of character in the physical world. Through a qualitative narrative study approach, teachers’ experiences and strategies are analyzed to shape their educational practices. The findings identify three primary functions of teachers: digital gardener, ethical anchor, and ecological bridge. The study concludes that the ecological transformation led by teachers is crucial in shaping generations who are digitally literate, spiritually resilient, and ethically robust, ready to face the challenges of the times. This research contributes to the development of character education, educational technology, and ecological ethics in the 21st century.